2022
DOI: 10.6065/apem.2244186.093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iodine intake on the pathogenesis of autoimmune thyroid disease in children and adults

Abstract: Thyroid hormone (TH) regulates the body's metabolism and iodine, a vital trace mineral, is vital for TH synthesis. As a TH biosynthesis catalyst, iodine has a substantial role in our health. When there is a modest iodine deficit, the thyroid gland grows autonomously, resulting in thyrotoxicosis. Those who consume excessive iodine risk developing hypothyroidism and thyroid autoimmunity. A transient hyperthyroid condition may rapidly increase iodine consumption. Iodine deficiency is common across the globe, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A shortened time to remission of all clinical signs in cats treated with the combined therapy may be related to the anti-inflammatory effect of KI linked to cytokine regulation [65], and/or to a beneficial interaction between ITZ and KI that has not been fully elucidated yet. In addition, excessive iodine supplementation in humans, as well as in cats, may affect the thyroid function, which might have an impact on the host immune response, but this has not been explored with the use of KI in the treatment of sporotrichosis [66][67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…A shortened time to remission of all clinical signs in cats treated with the combined therapy may be related to the anti-inflammatory effect of KI linked to cytokine regulation [65], and/or to a beneficial interaction between ITZ and KI that has not been fully elucidated yet. In addition, excessive iodine supplementation in humans, as well as in cats, may affect the thyroid function, which might have an impact on the host immune response, but this has not been explored with the use of KI in the treatment of sporotrichosis [66][67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms of excess iodine-induced thyroid enlargement include autoimmune-mediated lymphocytic infiltration of the thyroid gland or a compensatory increase in TSH levels due to decreased thyroid hormone synthesis, leading to stimulation and proliferation of the thyroid gland ( 35 , 36 , 37 ). However, in this study, thyroid parenchymal changes suggestive of lymphocytic infiltrations were not observed, and TSH levels were not associated with Tvol, which may be explained by the young age and the small sample size of our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the thyroid gland will not be able to effectively take up and utilize iodine for hormone production. Generally, this effect is transient, as the thyroid gland resumes its normal function once iodine concentrations drop back to normal [15]. However, in some cases, the Wolff-Chaikoff effect persists, causing long-term hypothyroidism [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have linked diet to the etiology of various diseases, including cardiometabolic and autoimmune diseases and psychological disorders [14][15][16]. Because individuals do not consume a single or limited number of nutrients, but consume different types of foods, it is important to study the whole diet rather than a single nutrient to obtain a holistic overview of what individuals consume.…”
Section: Introductionmentioning
confidence: 99%